COLLABORATIVE WRITING THROUGH GOOGLE DOCS IN ENGLISH LANGUAGE LEARNING: A STRUCTURED NARRATIVE REVIEW AND PEDAGOGICAL SYNTHESIS - Ulfah Sari Rezeki; Gemala Widiyarti; Muhammad Zulhairi Bin Zubairi (SENSEI RESEARCH CENTER, 2025)
Writing in English is difficult if the students do it alone, so they can be asked to write together. Nowadays this can be done using Google Docs because the students can write in the same document at the same time. This article discusses collaborative writing through Google Docs in English language learning. The method used is literature review from various journals. The result shows that Google Docs can help the students in writing together and they can also see the revision of their friends. However, sometimes only one or two students are active and the others are just watching. Therefore the teacher must design the task well and monitor the process.